Aromatase-deficient (ArKO) mice have a phenotype of increased adiposity - Jones, Margaret E. E. (The National Academy of Sciences, 2000)
The aromatase-knockout (ArKO) mouse provides a useful model to examine the role that estrogens play in development and homeostasis in mammals. Lacking a functional Cyp19 gene, which encodes aromatase, the ArKO mouse cannot synthesize endogenous estrogens. We examined the adipose depots of male and female ArKO mice, observing that these animals progressively accumulate significantly more intraabdominal adipose tissue than their wild-type (WT) littermates, reflected in increased adipocyte volume at gonadal and infrarenal sites. This increased adiposity was not due to hyperphagia or reduced resting energy expenditure, but was associated with reduced spontaneous physical activity levels, reduced glucose oxidation, and a decrease in lean body mass. Elevated circulating levels of leptin and cholesterol were present in 1-year-old ArKO mice compared with WT controls, as were elevated insulin levels, although blood glucose levels were unchanged. Associated with these changes, a striking accumulation of lipid droplets was observed in the livers of ArKO animals. Our findings demonstrate an important role for estrogen in the maintenance of lipid homeostasis in both males and females.